2019
DOI: 10.3390/beverages5020027
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Drinking and Emotions: Are There Key Sensory Drivers for Emotions?

Abstract: In the past couple of decades the coffee market has exploded, and to remain competitive, it is important to identify the key drivers for consumer acceptance of coffee. This study expanded on the previous emotion study on a population of coffee drinkers in Manhattan, Kansas, USA and focused on identifying the sensory drivers of emotional responses elicited during the coffee drinking experience (CDE). A trained coffee panel performed a descriptive analysis of six coffee samples and identified the key sensory att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
7
21
0
Order By: Relevance
“…Sample M3 was rejected by consumers due to sensory characteristics Burnt‐A, Lime‐F and Cinnamon‐F. This result agrees with Bhumiratana et al () whom indicated that attributes related to citrus fruits are considered as negative sensory drivers because they induce the sensation of umbalance.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Sample M3 was rejected by consumers due to sensory characteristics Burnt‐A, Lime‐F and Cinnamon‐F. This result agrees with Bhumiratana et al () whom indicated that attributes related to citrus fruits are considered as negative sensory drivers because they induce the sensation of umbalance.…”
Section: Resultssupporting
confidence: 85%
“…Class 2 preferred samples M4 and M5 (located in the region of preference of 20 to 40%, blue hue) because they have greater intensity of Sugar cane‐A, Sugar cane‐F, and Spicy‐AT. According to Geel, Kienner, and Kock () and Bhumiratana, Wolf, Chambres, and Adhikari () the bitter sensory attribute contributes to the preference of consumers of instant coffee. Sample M3 was rejected by consumers due to sensory characteristics Burnt‐A, Lime‐F and Cinnamon‐F.…”
Section: Resultsmentioning
confidence: 99%
“…The results generated by each rapid technique after applying the TOPSIS methodology are shown in Table 5. The sensory attributes considered (−) agreed with those reported by Bhumiratana et al 26 and Ramírez-Rivera et al, 10 who mentioned that the sensory attributes related to citrus, spicy, smoke, and burnt in roasted coffees in the USA and Mexico are considered negative. Positive attributes cocoa, coffee, bitter, sweet, caramel, and cinnamon can drive positive consumer emotions, such as good, pleasant, satisfied, driven, and special.…”
Section: Comparison Of Sensory Vocabulary After the Topsis Techniquesupporting
confidence: 82%
“…Positive attributes cocoa, coffee, bitter, sweet, caramel, and cinnamon can drive positive consumer emotions, such as good, pleasant, satisfied, driven, and special. 26 The generation of both (+) and (−) sensory attributes between the techniques were similar (K-W = 3.84, P > 0.05). This result was also found by Blancher et al, 28 who evaluated the texture of jellies using the rapid technique free sorting task.…”
Section: Comparison Of Sensory Vocabulary After the Topsis Techniquementioning
confidence: 84%
See 1 more Smart Citation